2018
DOI: 10.1186/s40413-018-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 immunity in asthma

Abstract: Type 2-immunity represents the typical adaptive response to allergen exposure in atopic individuals. It mainly involves Th2 cells and immunoglobulin E, as the main orchestrators of type 2-inflammation. Recently, it has been highlighted that allergens may be responsible for a Th2 response beside specific IgE activation and that a number of other environmental stimuli, such as viruses and pollutants, can trigger the same pattern of inflammation beyond atopy. Emerging data sustain a substantial role of the so-cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 117 publications
(130 reference statements)
0
128
0
4
Order By: Relevance
“…In the last decade, several biological treatments were introduced and investigated in the field of severe asthma, with the aim of reducing exacerbations and OCS use. A more and more detailed knowledge of asthma pathophysiology paved the way to the development of targeted molecules, in particular within the frame of Th2 inflammation, which includes interleukin (IL) 4, IL-5, IL-9, IL-13 and airway epithelial cells or innate lymphoid cells-2 [14][15][16][17], In such case, the inflammatory background is responsive to ICS [18], which promote eosinophil apoptosis [19]. Eosinophils exert a pivotal role in bronchial inflammation and represent one of the main targets for biological drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several biological treatments were introduced and investigated in the field of severe asthma, with the aim of reducing exacerbations and OCS use. A more and more detailed knowledge of asthma pathophysiology paved the way to the development of targeted molecules, in particular within the frame of Th2 inflammation, which includes interleukin (IL) 4, IL-5, IL-9, IL-13 and airway epithelial cells or innate lymphoid cells-2 [14][15][16][17], In such case, the inflammatory background is responsive to ICS [18], which promote eosinophil apoptosis [19]. Eosinophils exert a pivotal role in bronchial inflammation and represent one of the main targets for biological drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of asthma is associated with many factors such as heredity, an immune disorder, and environmental problems. In particular, the severe immune disorder is the main feature of the pathophysiological process of asthma (Caminati, Pham, Bagnasco, & Canonica, ). We first found that mogroside V can attenuate OVA‐induced AHR and decrease the number of inflammation‐related cells (eosinophils and macrophages) in the BALF of asthmatic mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the variation in symptoms, treatment response, impact on lung function and age at onset that the underlying mechanisms, involving many cell types and cytokines, vary between individuals as well as over time . Although these pathways and the interactions of mediators are complex, asthma can be roughly categorised into two types: eosinophilic asthma, the more common, which is associated with a type 2 immune response in which eosinophils and IgE are key contributors; and non‐type 2 non‐eosinophilic asthma, in which neutrophil airway infiltration is dominant or there is little infiltration.…”
Section: Asthma and Type 2 Inflammationmentioning
confidence: 99%
“…IL‐4 is involved in the regulation of B cells and IgE synthesis; IL‐5 is essential for the survival and maturation of eosinophils; and the functions of IL‐13 include regulation of IgE synthesis and a role in airway hyper‐responsiveness. Eosinophils also promote the synthesis and release of these and other cytokines …”
Section: Asthma and Type 2 Inflammationmentioning
confidence: 99%